Fast multigram scale microwave-assisted synthesis of vitamin E and C10-, C15-analogues under vacuum. Issue 68 (4th July 2016) - Rotolo, L.; Calcio Gaudino, E.; Carnaroglio, D.; Barge, A.; Tagliapietra, S.; Cravotto, G.
Abstract : A novel protocol for the microwave-assisted synthesis of (all- rac )-α-tocopherol, including its C10 - and C15 -analogues, is reported. Abstract : A novel protocol for the microwave-assisted synthesis of (all- rac )-α-tocopherol, including its C10 - and C15 -analogues, is reported. A rotating microwave reactor working under vacuum favoured the rapid evaporation of condensation water and solvent at the end of the process. The main advantages of this fast procedure are its good yield, selectivity, versatility, lower solvents and energy consumption, easier workup and-scalability.